Maca extracts regulate glucose and lipid metabolism in insulin‐resistant HepG2 cells via the PI3K/AKT signalling pathway - Li, Aimin (Food Sci Nutr, 2021)
This work focused on the separation of the active ingredients of maca (Lepidium meyenii Walpers) and evaluated the antioxidative capability of these components with effects on improving glucose and lipid metabolism in insulin‐resistant HepG2 cells. DPPH free radical scavenging and reducing power assays were used to evaluate the antioxidant activity of maca extracts. An insulin‐resistant HepG2 cell model induced by glucose, fructose, oleic acid, and palmitic acid was adopted to investigate the effects of maca extracts on regulating glucose and lipid metabolism in this study. LC‐MS/MS was then used for determination of the maca n‐butanol (NBT) subfraction. The results showed that maca ethanol extract and subfractions of this extract exhibited certain antioxidant capacity. Furthermore, the NBT subfraction reversed the disorders in glucose and lipid metabolism in insulin‐resistant HepG2 cells and significantly increased the mRNA expression of phosphoinositide 3‐kinases (PI3K) and AKT in insulin‐resistant HepG2 cells in a dose‐dependent manner. In addition, the LC‐MS/MS results showed that the NBT subfraction contained many active ingredients. Overall, this study suggests that the NBT subfraction of the ethanol extract rich in glucosinolates modulates insulin resistance via PI3K/AKT activation in insulin‐resistant HepG2 cells and might exert potentially beneficial effects in improving or treating glucose and lipid metabolic disorders.